Growth and Genetic Parameters of Mindi (Melia azedarach Linn.) Progeny Test in Parungpanjang Forest Research Station, Bogor - NFN Danu; Yulianti Bramasto; Dede J. Sudrajat (Jurnal Perbenihan Tanaman Hutan, 2021)
Mindi (Melia azedarach Linn., family Meliaceae) is a multipurpose forest tree species such as for furniture, vinier and plywood, otherwise the leaves for pesticide and medicine material. Mindi mostly cultivated in a community forest, especially in West Java. This study was aimed to assess the growth performance and genetic parameter of the progeny test of mindi at Parungpanjang Forest Research Station, Bogor, West Java. The progeny test was established by using a randomized complete block design, consisting of 6 blocks and 73 families and each family consisting of 4 trees row-plot. The survival at 7 years old was 57.48%, height was 7.15 m and diameter is 8.59 cm, in average. The height and diameter growths among families showed a significantly different. The best family growth in height and diameter were Sumedang-31 and Bogor-18 families, respectively.The individual and family heritabilities for both stem diameter and  tree heght characters were stil relatively low, with the higher family heritability value than individual heritability.  The genetic correlation between total height and stem diameter of 0.57 indicates a strong correlation between the traits.